Disturbance of Almoravid conditions in Maghreb and Andalusia, careful reading of the causes of the fall and disappearance - chaki, abdelaziz (Journal of Social Sciences and Humanities, 2021)
The state of Almoravid in Maghreb and Andalusia set a good example by bringing forth the right Islam and defending the Muslims there against the Christian forces. However, it begins to get weakened until it is declined in 541 AH. The factors of the decline were multiple: the absence of personality to the governors, the life of debauchery and the passivity of the emirs, the conflict about the sovereignty, the tolerance of the emir Ali Bin Yousef with the rebellion threatening the state in parallel with the economic crisis that hit the state. Not to mention external factors such as revolutions and insurrections in the Andalusian cities. The army of the Almoravids has been weakened by the confrontation of Christians. But the main cause was the revolution of the Almohads who attacked and captured the city of Marrakech and defeated the monarch of the Almoravids.